"Can you come tell people to be quiet?": Analyzing chat questions from on-campus and off-campus patrons. Issue 3 (1st October 2020) - Skaggs, Danielle
Abstract: Chat reference is popular with both on and off campus users as well as distance students. This article presents the results of a chat transcript analysis project that used fall semester 2019 transcripts to compare question types and disconnect issues for on campus, off campus, and distance students.